Cumulative Damage in Juvenile Idiopathic Arthritis: A Multicenter Study From the Pediatric Rheumatology Arab Group. Issue 4 (13th March 2021) - Al‐Mayouf, Sulaiman M.; Hashad, Soad; Khawaja, Khulood; Alrasheedi, Abeer; Abdwani, Reem; Abushhaiwia, Awatif; AlSuwaiti, Muatasem; Alzyoud, Raed; AL Abrawi, Safiya; Asiri, Abdulrahman; Alshaikh, Manal; Sharif, Elsadeg; et al.
Abstract : Objective: To report the cumulative articular and extraarticular damage in Arab children with juvenile idiopathic arthritis (JIA) and to identify variables that correlate with disease damage. Methods: We conducted a multicenter, cross‐sectional study among 14 pediatric rheumatology centers from 7 Arab countries. JIA patients who met the International League of Associations for Rheumatology classification criteria and had a disease duration of >1 year were enrolled. Disease activity status was assessed using the Juvenile Arthritis Multidimensional Assessment Report. Disease damage was assessed by the Juvenile Arthritis Damage Index, articular (JADI‐A) and extraarticular (JADI‐E). Results: A total of 702 (471 female) JIA patients with a median age of 11.3 years (interquartile range [IQR] 8.0–14.0 years) were studied. Median age at disease onset was 5 years (IQR 2.0–9.0 years) and the median disease duration was 4 years (IQR 2.0–7.0 years). The most frequent JIA categories were oligoarticular JIA (34.9%), polyarticular JIA (29.5%), and systemic JIA (24.5%). Clinical remission was achieved in 73.9% of patients. At the last clinic visit, 193 patients experienced joint damage, with a mean ± SD JADI‐A score of 1.7 ± 4.5, while 156 patients had extraarticular damage, with a mean ± SD JADI‐E score of 0.5 ± 1.1. Patients with enthesitis‐related arthritis had the highest JADI‐A score. JADI‐A correlated significantly with the presence of a family history of JIA. JADI‐A and JADI‐E had a significant correlation with long disease duration. Conclusion: Cumulative damage was common in this Arab JIA cohort, and consanguinity and JIA in a sibling were frequent findings and were associated with a greater cumulative damage.